Simulation and optimization of coal gasification in a moving-bed reactor to produce synthesis gas suitable for methanol production unit - Shamsi, Mehdi (Array, 2020)
This paper presents process simulation and optimization of coal gasification process in a moving-bed reactor using Pittsburgh No. 8 coal as feed. The system of differential equations for the mass and energy balances was solved using 4th-order Runge-Kutta method and optimized by non-dominated sorting genetic algorithm-II (NSGA-II) method. The simulation was used to predict solid and gas temperature profile and gas composition along the reactor. The simulation results were compared successfully with experimental data relevant to Westfield plant in Scotland. In addition, the effect of operating parameters such as coal-to-oxygen molar ratio, steam-to-oxygen molar ratio, inlet gas temperature, reactor pressure, and oxygen mole fraction in inlet air on amount of synthesis gas (syngas) production, hydrogen to carbon monoxide molar ratio (HCMR) in produced syngas, and coal conversion was investigated. Finally, the reactor performance was optimized to produce the highest syngas production with a HCMR of two using NSGA-II method.